Pelatihan Pilah Sampah pada Guru PAUD (Pendidikan Anak Usia Dini) yang Tergabung dalam Gugus Abimanyu dan Gugus Banowati Kota Semarang - Hastarini Dwi Atmanti; Tri Wahyu Rejekiningsih; Aris Anwaril Muttaqin; Rifaldi Majid; Novita Mukti Rinusara (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
The purpose of this community service project is to train kindergarten teachers who belong to the Abimanyu and Banowati groups in waste sorting. The Community Based Participatory Research (CBPR) approach is used to carry out community service. Using this approach, kindergarten teachers and researchers work together to teach kids how to sort waste. Since waste sorting is a novel approach to waste management, it needs to be promoted and established in society, particularly among students. Most of the kindergarten teachers who took part in the program had never instructed their kids in waste sorting. Teachers of kindergarten received instruction on how to segregate waste in bins with red, yellow, and green lids. Kindergarten teachers can more easily teach sorting bins with colored lids to their kids. By imparting good values linked to teaching discipline, upholding cleanliness, and recognizing the health of their pupils, waste sorting training helps kindergarten teachers understand the significance of waste sorting.